Diversity Of Corynespora Cassiicola Isolates And Changes In Rubber (Hevea Brasiliensis) Leaf Protein Profiles In Response To Pathogen Inoculation - Nghia, Nguyen Anh (2009)

(untitled)
Corynespora leaf fall, caused by Corynespora cassiicola, is one of the most important diseases in rubber (Hevea brasiliensis) plantations. A study was conducted to analyse the diversity among C. cassiicola isolates and to investigate the changes in rubber leaf protein profiles in response to this pathogen. Inter Simple Sequence Repeat (ISSR) and rDNA-ITS sequence markers along with morphological characteristics and detached leaf assay were employed to analyse 21 isolates of C. cassiicola collected from different rubber clones grown in several states of Malaysia. Variations in morphological features were observed within and among isolates with no inclination to either clonal or geographical origins of the isolates. The ISSR and rDNA-ITS sequence analyses segregated the studied isolates into two distinct groups. Group 1 includes 12 isolates from the states of Johor and Selangor (this group was split into 2 subgroups 1A and 1B, subgroup 1B includes a unique isolate, CKT05D); and group 2 includes 9 isolates obtained from the other states. AMOVA analysis showed 84% of total genetic variation was attributed to variation between two groups with highly significant difference. The detached leaf assay performed on selected rubber clones grouped the isolates in subcluster 1A into Race 1; the isolates in cluster 2 into Race 2 while the pathogenicity of the isolate CKT5D was dissimilar to either Race 1 or Race 2. Two Single Nucleotide Polymorphisms (SNPs) were discovered from the rDNA-ITS region of the studied isolates. They are correlated to the races that were identified in Malaysia. The BLAST search results revealed that the nucleotide sequences in the rDNA-ITS region of C. cassiicola fungus are highly conserved. Seven SNPs and two indels were detected in the rDNA-ITS region of the studied and deposited C. cassiicola isolates obtained from several countries on diverse hosts and their presence may be correlated with the race of this fungus. The changes in the leaf protein profiles of two rubber clones RRIM 600 and PB 260 in response to inoculation with the spores of two isolates representing two races of this fungus were analysed using two-dimensional gel electrophoresis (2-DE). Several differentially expressed proteins were detected at different time points after inoculation. Dissimilarities in expression patterns were observed within and among the four clone/isolate interaction systems. The number of differentially expressed proteins was also different among the systems. These proteins differed in their estimated isoelectric points (pI) and molecular weights (MW) with the exception of three detected identical proteins. In conclusion, morphological analysis could identify but not differentiate the races of C. cassiicola; ISSR markers proved useful to distinguish the races while rDNA-ITS sequence markers could not only identify but could also infer the races of this fungus. This study confirmed that at least two distinct groups of C. cassiicola infect rubber trees in Malaysia. The changes in the 2-DE protein profiles of the rubber leaf proteomes in response to inoculation with C. cassiicola are highly dependent on the compatibility reactions of the rubber clone to a particular isolate. Differences in protein profiles implied the complexity of the interactions.